Methodik zur virtuellen Absicherung der formgebenden Operation des Nasspressprozesses von Gelege-Mehrschichtverbunden - Senner, Thomas (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2016)
The manufacturing process of carbon fibre reinforced plastic parts may lead to wrinkles and fibre waviness in the final part. These imperfections in the fibre orientation can result in parts that do not fulfill their functional requirements. In this book, a methodology is presented which enables predicting wrinkles. Thus, the methodology allows a virtual design of the manufacturing process in an industrial environment. An essential part of this approach is a modelling which improves the predictive quality regarding wrinkles compared to the state of the art. Furthermore, an analysis and a model of an innovative restraining system is described that is capable to prevent the formation of wrinkles. Finally, two experimental methods are presented which allow characterising the fibre orientation in the intermediate plies of multi-layer composite